The Effectiveness of Symbolic Modeling Learning to the Early Children’s Expressive Language Skills - Asmiarti, Dwi; Aeni, Kurotul; Mulawarman, Mulawarman (Universitas Negeri Semarang, 2020)
Early children need language to express their ideas. Thus, they will need to master expressive language skills. This research aims to find out the effectiveness of the symbolic modeling learning model assisted by using a doll toward the early children’s expressive language skills. This is experimental research with a pretest-posttest control group design. The population of the research consisted of 30 children aged 5-6 years old in PGRI Sarimulyo and PGRI Sarimulyo 02 preschools. The data were taken by purposive sampling on 30 children aged 5-6 years old. The data collection technique was observation sheets of expressive language skills with a 1-4 liker scale. Wilcoxon test and the Mann Whitney test were applied to test the hypothesis. The result show that the symbolic modeling method assisted by a doll is effective for the students learning outcomes after being intervened. It proves that the symbolic modeling method assisted by a doll is effective to improve the expressive language skills of early childhood children at PGRI Sarimulyo Kindergarten